Snoring Beauty - Hale, Bruce; Fine, Howard, 1961- (Orlando : Harcourt, 2008)
An adaptation of the traditional tale, featuring a sleeping, snoring princess who is rescued by a prince after being cursed by a bad fairy.
Booklist
School Library Journal
Wilson's Children
Booklist, May 2008
Horn Book, October 2008
Kirkus Review, April 2008
Keywords: Fairy tales; Folklore -- Germany; Fairy tales; Folklore -- Germany; Fairy tales; Folklore -- Germany; Picture books for children